Analysis of School Principals’ Strategic Management in Implementing The Merdeka Curriculum at Public High Schools in East Kalimantan Province, Indonesia - Akhmad, Akhmad; Anggreini, Putri; Haeruddin, Haeruddin (PT ARRUS Intelektual Indonesia, 2025)
Strategic management is the process of decision-making and policy implementation to take actions and evaluate what has been done effectively to achieve specific goals. As leaders and decision-makers in schools, principals are thus required to have a good understanding of the policy regarding the implementation of the Merdeka Curriculum. The objective of this research is to analyze and describe strategic management, including strategic planning, implementation, and evaluation, in the implementation of the Merdeka Curriculum in public high schools in East Kalimantan Province. The method used was a survey to gather information on the implementation of the Merdeka Curriculum using questionnaires. The research findings indicate that out of 129 responding principals, 92% chose the Self-Transformation option, 98% engaged in strategic planning, 94% undertook strategic implementation, and 93% conducted strategic evaluation/control in the implementation of the Merdeka Curriculum. Based on these findings, it can be concluded that principals have a good understanding and knowledge of strategic management implementation, including strategic planning, implementation, and evaluation/control, in the implementation of the Merdeka Curriculum in public high schools in East Kalimantan Province.